A produção do depoimento especial e o direito processual penal - Manssur, Maria Domitila Prado (2025)
The present work is guided by the identification of the vulnerable person in the criminal process and by the reasons that justify his/her inclusion in a protection system established, especially for his/her hearing, in the both phases of criminal prosecution – as a victim or as a witness of violence –, without risk to the balance between prosecution and defense. The analysis of protective listening, from the perspective of comparative law, taking into account countries that adopt procedural systems originated in common and civil law, allows the conclusion that efficiency and guaranteeism are confirmed in the application of criminal law, after due legal process, respecting the accused and the victims fundamental rights and witnesses heard, regardless the legal system adopted. In prestige to the special statement, rises the need to face impunity caused by underreporting of crimes and silence of the vulnerable people, especially due to age, who, subjected to the traditional hearing method, often fail to reveal witnessed or suffered violence. The Law n. 13.413/2017 integrates specialized listening and special testimony with the pre-existing vulnerable person protective system. It is presented as a guideline for the Gender-Responsible Judgment Protocol, whose adoption is determined in the trials of the entire Judiciary, determined by Resolution n. 492/2023 of the National Council of Justice. In this step, the principle of the judge’s integrity, which guides the interpretation of the law to morals and social aspirations, contributes to the conclusion of the strong value of victims and witnesses’ words as evidence of violence in the criminal process. There is identification of criminal offenses committed, recurrently, against vulnerable, due to age, proving indispensable the alignment between professionals of Law, Psychology and Social Work, concerning their respective competencies and ethical limitations, joining efforts to, in stages of criminal prosecution, allow the disclosure of facts relevant to the Law, in accordance with the children and adolescents dignity and their best interests, guaranteed by the Federal Constitution